Prevalence and characteristics of progressive fibrosing interstitial lung disease in a prospective registry. Issue 4 (6th October 2022) - Hambly, Nathan; Farooqi, M. Malik; Dvorkin-Gheva, Anna; Donohoe, Kathryn; Garlick, Kristopher; Scallan, Ciaran; Chong, Sy Giin; MacIsaac, Sarah; Assayag, Deborah; Johannson, Kerri A.; Fell, Charlene D.; Marcoux, Veronica; et al.
Background: Progressive fibrosing interstitial lung disease (PF-ILD) is characterised by progressive physiological, symptomatic and/or radiographic worsening. The real-world prevalence and characteristics of PF-ILD remain uncertain. Methods: Patients were enrolled from the Canadian Registry for Pulmonary Fibrosis between 2015 and 2020. PF-ILD was defined as a relative forced vital capacity (FVC) decline ≥10%, death, lung transplantation or any two of: relative FVC decline ≥5% and <10%, worsening respiratory symptoms or worsening fibrosis on computed tomography of the chest, all within 24 months of diagnosis. Time-to-event analysis compared progression between key diagnostic subgroups. Characteristics associated with progression were determined by multivariable regression. Results: Of 2746 patients with fibrotic ILD (mean±sd age 65±12 years; 51% female), 1376 (50%) met PF-ILD criteria in the first 24 months of follow-up. PF-ILD occurred in 427 (59%) patients with idiopathic pulmonary fibrosis (IPF), 125 (58%) with fibrotic hypersensitivity pneumonitis (HP), 281 (51%) with unclassifiable ILD (U-ILD) and 402 (45%) with connective tissue disease-associated ILD (CTD-ILD). Compared with IPF, time to progression was similar in patients with HP (hazard ratio (HR) 0.96, 95% CI 0.79–1.17), but was delayed in patients with U-ILD (HR 0.82, 95% CI 0.71–0.96) and CTD-ILD (HR 0.65, 95% CI 0.56–0.74). Background treatment varied across diagnostic subtypes, with 66% of IPF patients receiving antifibrotic therapy, while immunomodulatory therapy was utilised in 49%, 61% and 37% of patients with CHP, CTD-ILD and U-ILD, respectively. Increasing age, male sex, gastro-oesophageal reflux disease and lower baseline pulmonary function were independently associated with progression. Conclusions: Progression is common in patients with fibrotic ILD, and is similarly prevalent in HP and IPF. Routinely collected variables help identify patients at risk for progression and may guide therapeutic strategies. In the setting of fibrotic ILD, disease progression was observed in 50% of prospectively evaluated patients at 24 months. Highest rates were seen in those with IPF (59%) and HP (58%), followed by U-ILD (51%) and CTD-ILD (45%). https://bit.ly/3v7T9ux